A measurement of student teachers' parent–teacher communication competences: the design of a video-based instrument. Issue 3 (27th May 2018) - De Coninck, Karen; Valcke, Martin; Vanderlinde, Ruben
Abstract: This study reports on the design of a video-based instrument to assess student teachers' parent–teacher communication competences (PTCC) in a reliable and valid way. PTCC refer to the competences needed to communicate successfully with parents during conversations such as parent–teacher conferences. Taking into account both conceptual and methodological challenges regarding the measurement of competences, several methodological steps were followed to design a video-based instrument focusing on the assessment of student teachers' perception, interpretation and decision-making skills (PID skills) regarding parent–teacher communication: designing video vignettes presenting realistic job situations regarding parent–teacher communication; developing instructions to elicit student teachers' PID skills; designing a coding scheme to analyse student teachers' responses; and implementing the instrument ( n = 269) to test and refine it. This ultimately resulted in an instrument consisting of (1) three video vignettes, (2) a series of open-ended questions eliciting student teachers' PID skills, and (3) three coding schemes to develop a perception score, an interpretation score and a decision-making score for PTCC. The (4) implementation of the instrument confirmed that this innovative video-based tool might be a promising approach to assess student teachers' PTCC. To conclude, the quality and contribution of the measurement instrument and the implications for further research are discussed.